Forecasting of Water Table Fluctuations Using MODFLOW Numerical Model from 1387 to 1437 in Garbaygan Aquifer - Ahmad Fatehi Marj; Majid Taie Semiromi; Abdol Nabi Kolahchi; Seyed Khallagh Mirnia (علوم و مهندسی آبیاری, 2011)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 11pt; mso-bidi-language: AR-SA; mso-fareast-font-family: Calibri; mso-bidi-font-size: 13.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Sustainable management of groundwater resources in underdeveloped regions is one of the essential objectives for the future, especially when the rising demand for clean drinking water by these fast growing communities is considered. Uncontrolled expansion of industries, agriculture and settlements as well as insufficient management imposed on groundwater resources are main reason for proper management methods. Based on capability of good match advanced models in groundwater simulation with hydraulic system of aquifer and prediction of future situations created suitable conditions for management and exploitation these resources. Objects of present research is evaluating of precision of MODFLOW mathematical model in order to representative of proper management in groundwater resources in Garbaygan plain as a region with strategic importance in farming. To start doing this study, input layers of model was created by using geographic information system (GIS). Afterwards boundary condition and discertization of aquifer have determined. Also calibration in steady and transient state was done by using available information. In order to confidence of simulation results, verification test did on data rest. Therefore representative hydrograph and water table contour in 10, 30 and 50 future years (1397, 1417 and 1437) was forecasted. Result showed that drawdown trend of representative hydrograph will be 0.331, 0.298 and 0.27 meters per year in 10, 30 and 50 future years respectively. So it understands that drawdown trend will decrease with increase of forecasted period.